Proteomic analysis of moroccan cobra naja haje legionis venom using tandem mass spectrometry - Malih, Ibitissam; Ahmad Rusmili, Muhamad Rusdi; Ting, Yee Tee; Saile, Rachid; Ghalim, Noreddine; Othman, Iekhsan (Elsevier Ltd., 2014)
The proteome of the venom of Naja haje legionis, the only medically important elapid species in Morocco, has been elucidated by using a combination of proteomic techniques that includes size exclusion chromatography, reverse-phase HPLC, Tricine/SDS-Page, tryptic digestion, Q-TOF tandem mass spectrometry and database search. The sequence analysis of venom fractions revealed a highly complex venom proteome which counts a total of 76 proteins identified from database that can be assigned into 9 proteins families. We report the identification of: cobra venom factor (CVF), l-amino-acid oxidases (LAAO), acetylcholinesterase (AChE), snake venom metalloproteinases (SVMP), cysteine rich secretory proteins (CRISP), venom nerve growth factor (vNGF), phospholipases A2 (PLA2), vespryns, kunitz-type inhibitor, short neurotoxins, long neurotoxins, weak neurotoxins, neurotoxin like proteins, muscarinic toxins, cardiotoxins and cytotoxins. Comparison of these proteins showed high sequence homology with proteins from other African and Asian cobras. Further works are needed to assess the contribution of individual toxins in venom toxicity.